ANALYSIS OF QUR'ANIC ILLITERACY ERADICATION THROUGH IMLA': A CASE STUDY OF ARABIC LANGUAGE EDUCATION STUDENTS AT ISLAMIC UNIVERSITY STATE OF NORTH SUMATERA - Nur Haliza; Sukma Indriati; Togar Siagian (Yayasan Haiah Nusratul Islam, 2024)
This study describes the eradication of Qur'anic illiteracy through Imla' in Arabic Language Education Students. The type of research in this paper is descriptive qualitative research. Data collection techniques are carried out by means of participant observation and in-depth interviews, documentation, and material research which aims to determine the authenticity of the material and investigate it. The results of this study are that there are still student errors in writing Al-Qur'an verses due to difficulties in connecting words and lack of nahwu dah Sharaf. Therefore, it is necessary to pay attention to the rules of writing in order to avoid errors in writing. Eradicating Qur'anic illiteracy through imla' is so that students can maintain the writing of the Qur'an, especially for memorizers of the Qur'an, not only being able to read or memorize properly and correctly but also having to write these verses according to the rules of writing. As Muslims, we must be able to maintain the sanctity of the Qur'an including from errors in writing the Qur'an in order to reduce the level of illiteracy in the Qur'an.